Can Three Months of Teriparatide Be One of Treatment Options for Osteoporotic Vertebral Compression Fracture Patients? - Kang, Jung Hoon (Korean J Neurotrauma, 2019)
OBJECTIVE: Osteoporosis is one of the most common causes of vertebral compression fractures (VCFs). Teriparatide, a recombinant human parathyroid hormone, is the first anabolic agent for the treatment of osteoporosis. The aim of this study was to determine whether 3 months of teriparatide could be effective for patients with osteoporotic VCF at the thoracolumbar spine. METHODS: We reviewed 25 patients with thoracolumbar osteoporotic compression fractures between July 2012 and October 2016 who could be followed up for more than 1 year. Patients were divided into 2 groups depending on the use of teriparatide: 14 patients received teriparatide through subcutaneous injection (group I) and 11 patients did not receive teriparatide (group II). Demographic data, bone mineral density, hospitalization period, changes in the visual analogue scale (VAS) score, body mass index, and medical history such as smoking, alcohol, diabetes, and steroid usage were reviewed. Radiographs were also reviewed to evaluate vertebral body compression percentages and kyphotic angles. RESULTS: Overall changes of VAS score between injury and follow-up were statistically improved in both groups at 2 to 3 weeks post-injury. However, difference in VAS improvement at a specific time between the 2 groups was not statistically significant. Overall kyphotic angle and compression percentage between injury and follow-up time were increased in group II than those in group I, although the difference between the 2 groups was not statistically significant. CONCLUSION: Three-month of teriparatide did not show protective effects on progression of fractured vertebral body collapse or kyphotic changes in patients with osteoporosis.